Prevalence of Mycobacterium avium subsp. paratuberculosis in milk and dairy cattle in Southern Italy: preliminary results - Giacomo Marchetti; Matteo Ricchi; Andrea Serraino; Federica Giacometti; Elena Bonfante; Norma Arrigoni (Italian Journal of Food Safety, 2013)
Paratuberculosis affects all ruminants worldwide. Mycobacterium avium subsp. paratuberculosis (MAP) could have a role in human diseases like Crohn’s. Some extra European Union (EU) countries request importation of MAP-free products. Italy has not yet actualised a control programme and the diffusion of the infection is still unknown in Southern Italy. The aim of this study was to evaluate the prevalence of the infection in five regions of Southern Italy. Bulk tank milk and in-line milk filters were sampled in 780 dairy cattle herds and respectively analysed by ELISA and real time-polymerase chain reaction (PCR). One hundred and 55 out of 780 herds (19.9%) were found positive by ELISA and/or real time PCR. Individual milk samples were then collected from all the producing animals of positive herds and from a selection of negative herds. The estimated prevalence varies from region to region between 2.8 and 5.5%. Our results indicate that the disease is widespread in the five regions. The observed prevalence could be underestimated.